Unclear boundaries between dialect and language within the Igboid cluster: a focus on the syntax of tense, aspect, and modality in Delta Igboid - Idegbekwe, Destiny (Linguistik Online, 2026)
This study argues and draws attention to the tense aspects and modality (TAM) comparison of the three Delta Igboid varieties with the Standard Igbo. A study like this that accounts for the TAM systems in these languages can help establish a position in the literature on the verbal operating system in the languages. At the end of this study, there will be a more objective account of the features of TAM in the Delta Igboid varieties of Ika, Ukwuani, and Enuani. It is expected that this can further help settle the arguments about whether these Igboid varieties are distinct languages of their own or are offspring of the Igbo language. This work significantly contributes to the documentation of Delta Igboid variations by providing a comprehensive examination of the Tense, Aspect, and Modality (TAM) systems in Ika, Ukwuani, and Enuani. The research offers an objective basis for comprehending the structural features and linguistic categorisation of these types by analysing their verbal operational systems. The findings contribute to continuing discussions about whether these variants should be categorised as separate languages or as subvarieties within the overarching Igbo language.